Concentrating Ni, Co, and Mn ions with graphene nanoribbon membrane for spent lithium-ion battery recycle: Combined experimental and techno-economic study - Kim, Jiwon; Lee, Jong Hyup; Choi, Jongdu; Kim, Jeong Pil; Kim, Ju Yeon; Kang, Junhyeok; Kim, Junghwan; Kim, Dae Woo (Elsevier BV, 2025)
The growing demand for lithium-ion batteries (LiBs) driven by the rapid growth of the electric vehicle market is leading to the problem of end-of-life battery disposal, which greatly increases the need for efficient rare metal recycling of waste batteries. Ion enrichment using a membrane has a potential to improve the efficiency of the recycling process, resulting in low energy and cost consumption compared with conventional rare metal recovery methods. In this work, graphene oxide nanoribbon (GONR), synthesized by oxidizing multi-walled carbon nanotube (MWNT), was thermally annealed via hot-pressing to fabricate graphene nanoribbon (GNR) membranes. GNR membranes exhibit narrow and stable interlayer spacing, effectively inhibiting divalent ion permeation while maintaining water transport channels. Ion enrichment experiments demonstrated that GNR membranes are effective in concentrating the ionic solutions via forward osmosis (FO) process with a water flux of 1 LMH (L m-2 h-1) and water/ion selectivity of 10,500. The economic feasibility of the FO system in LIB recycle process was evaluated, showing a total annualized cost (TAC) reduction of 71.7 % and 14.3 % compared to the evaporation and reverse osmosis systems, respectively.